2016
DOI: 10.1016/j.jcma.2015.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Etiologies and outcome of osteonecrosis of the femoral head: Etiology and outcome study in a Taiwan population

Abstract: Alcohol use had the greatest impact on ONFH in our population. Nonidiopathic ONFH patients had the worst outcome. Understanding the nature of progression of ONFH and incidence of contralateral disease may provide great prognostic value to detect and perform early intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 19 publications
1
33
0
1
Order By: Relevance
“…Genetic factors may also play a significant role (10). Nonidiopathic osteonecrosis patients had the worst outcome (11). Patients with sickle cell disease have a high likelihood of progressing to head collapse.…”
Section: Patient Assessment and Classificationmentioning
confidence: 99%
“…Genetic factors may also play a significant role (10). Nonidiopathic osteonecrosis patients had the worst outcome (11). Patients with sickle cell disease have a high likelihood of progressing to head collapse.…”
Section: Patient Assessment and Classificationmentioning
confidence: 99%
“…12 Though exact mechanism is not known various theories have suggested role of increased adipocyte volume, increased intra-osseous pressure and fat embolism as final mechanisms. 13 Tsai et al 14 from Taiwan found that alcohol consumption was the most common etiology contributing to 45.2% cases of ONFH, followed by idiopathic AVN in 33.1% and steroid induced AVN in 21.7%. In total 59.1% cases were bilateral.…”
Section: Discussionmentioning
confidence: 99%
“…Avascular osteonecrosis is a pathological state where a reduced vascular supply leads to ischemia and bone necrosis. This have been reported in orthopedic literature [2,3] but only few cases described maxillary bone necrosis, in particular secondary to DIC. With regard to the oro-maxillo-facial sphere, avascular necrosis of the midface is a rare condition due to rich blood supply from the bilateral branches of the external carotide artery [4].…”
Section: Introductionmentioning
confidence: 97%